Corticospinal axons make direct synaptic connections with spinal motoneurons innervating forearm muscles early during postnatal development in the rat. (13th December 2015) - Maeda, Hitoshi; Fukuda, Satoshi; Kameda, Hiroshi; Murabe, Naoyuki; Isoo, Noriko; Mizukami, Hiroaki; Ozawa, Keiya; Sakurai, Masaki
Abstract : Key points: Direct connections between corticospinal (CS) axons and motoneurons (MNs) appear to be present only in higher primates, where they are essential for discrete movement of the digits. Their presence in adult rodents was once claimed but is now questioned. We report that MNs innervating forearm muscles in infant rats receive monosynaptic input from CS axons, but MNs innervating proximal muscles do not, which is a pattern similar to that in primates. Our experiments were carefully designed to show monosynaptic connections. This entailed selective electrical and optogenetic stimulation of CS axons and recording from MNs identified by retrograde labelling from innervated muscles. Morphological evidence was also obtained for rigorous identification of CS axons and MNs. These connections would be transient and would regress later during development. These results shed light on the development and evolution of direct CS–MN connections, which serve as the basis for dexterity in humans. Abstract: Recent evidence suggests there is no direct connection between corticospinal (CS) axons and spinal motoneurons (MNs) in adult rodents. We previously showed that CS synapses are present throughout the spinal cord for a time, but are eliminated from the ventral horn during development in rodents. This raises the possibility that CS axons transiently make direct connections with MNs located in the ventral horn of the spinal cord. This was tested in the present study. Using cervical cord slices prepared from rats on postnatal days (P) 7–9, CS axons were stimulated and whole cell recordings were made from MNs retrogradely labelled with fluorescent cholera toxin B subunit (CTB) injected into selected groups of muscles. To selectively activate CS axons, electrical stimulation was carefully limited to the CS tract. In addition we employed optogenetic stimulation after injecting an adeno‐associated virus vector encoding channelrhodopsin‐2 (ChR2) into the sensorimotor cortex on P0. We were then able to record monosynaptic excitatory postsynaptic currents from MNs innervating forearm muscles, but not from those innervating proximal muscles. We also showed close contacts between CTB‐labelled MNs and CS axons labelled through introduction of fluorescent protein‐conjugated synaptophysin or the ChR2 expression system. We confirmed that some of these contacts colocalized with postsynaptic density protein 95 in their partner dendrites. It is intriguing from both phylogenetic and ontogenetic viewpoints that direct and putatively transient CS–MN connections were found only on MNs innervating the forearm muscles in infant rats, as this is analogous to the connection pattern seen in adult primates. Key points: Direct connections between corticospinal (CS) axons and motoneurons (MNs) appear to be present only in higher primates, where they are essential for discrete movement of the digits. Their presence in adult rodents was once claimed but is now questioned. We report that MNs innervating forearm muscles in infant rats receive monosynaptic input from CS axons, but MNs innervating proximal muscles do not, which is a pattern similar to that in primates. Our experiments were carefully designed to show monosynaptic connections. This entailed selective electrical and optogenetic stimulation of CS axons and recording from MNs identified by retrograde labelling from innervated muscles. Morphological evidence was also obtained for rigorous identification of CS axons and MNs. These connections would be transient and would regress later during development. These results shed light on the development and evolution of direct CS–MN connections, which serve as the basis for dexterity in humans.